Determining the Effect of O2-partial Pressure on the Physical Properties of DC-magnetron Sputtered Cadmium Zinc Oxide thin Films - A. Guru Sampath Kumar; L. Obulapathi; P. Siva Kumar; V. S. Samyuktha (Research Trends and Challenges in Physical Science Vol. 4, 2021)
Cd-doped ZnO has a wide range of applications in solar cells and optoelectronic devices. Reactive dc magnetron sputtering at different O2 partial pressures (1-3sccm) on glass substrate was used to make Cd-doped ZnO thin films. The compound’s structure was determined using XRD, the microstructure was investigated using FE-SEM, the absorption spectra was measured using a UV-Vis-NIR spectrometer, and the electrical properties were investigated using the four probe method. XRD studies confirmed the hexagonal wurtzite structure in (002) orientation and also have the crystallite size of 14.08nm at 2.0sccm of PO2.The variation of optical band gap was reported in this study. The minimum resistivity is found when PO2=2.0 sccm.